Analysis of vaccination policy in the era of the COVID-19 pandemic in Indonesia - Mustari, Nuryanti; Junaedi, Junaedi; Parawu, Hafiz Elfiansya; Hawing, Hardianto; Herman, Herman; Syukri, Ulfiah; Amri, Aqmal Reza (International Journal of Public Health Science (IJPHS), 2024)
This study aims to reflect on the pattern of vaccination policies implemented by the Indonesian government and to analyze public sentiment (pro/con) towards vaccination policies and the government's strategy in formulating democratic policies, prioritizing the aspirations of those affected by the policies adopted. This paper uses qualitative research methods with NVivo 12 Plus as a data processing tool. This study's results indicate that vaccination policies tend to be mandatory in Indonesia with an indirect compulsory application polarization. Hence, the government still uses a coercive and restrictive approach to vaccination programs. In Indonesia, vaccination policy intersects with ethical aspects, especially religious values, resulting in diverse public sentiments.